Efficient Rhodamine B removal by N-doped hierarchical carbons obtained from KOH activation and urea-oxidation of glucose hydrochar. Issue 4 (August 2021) - Hou, Zhengqi; Tao, Yinping; Bai, Tiancheng; Liang, Ye; Huang, Shirong; Cai, Jinjun
Abstract: Organic dyes as one of the main pollutants in wastewater proposed harmful effects towards human life, and using carbons as adsorbents for efficient dyes removal from aqueous solution aroused great interest. Herein, N-doped hierarchical carbons with partial spheres were successfully obtained from urea oxidation of glucose hydrochar, followed by KOH activation. Surface areas of carbons largely increased from 1469 to 3282 m 2 g −1 as the etching temperature increased from 600° to 800° C, while N-species decreased from 7.23 to 1.26 at%. The as-made carbons had superior removal ability for Rhodamine B (RhB), and AHU-800 sample including surface areas of 3282 m 2 g −1, mesopores of 2.74 nm and 1.26 at% N-species had equilibrium amount of 2949 mg g −1 at 25 °C in 1000 mg L −1 solution up to 300 min, followed by a pseudo-second order model. The maximum capacity on AHU-800 was up to 5181 mg g −1 determined by Langmuir model, among the best results for carbon-based adsorbents. This present method contributed to large-scale production of high-quality sorbents for dye-bearing water, and the superior removal performance was owned to synergistic effects of high surface areas, hierarchically pores and pyrrolic N in the framework, endowing these carbons to be highly effective in water treatment application. Graphical Abstract: ga1 Highlights: Hierarchical carbons were obtained from urea oxidation and mild KOH activation. The surface areas of carbons were highly up to 3282 m 2 /g with mesopores of 2.74 nm. Langmuir model and pseudo-second-order expressed well for RhB adsorption. The maximum adsorbed RhB amounts were calculated to be of 5181 mg/g at 25 °C. The carbons still contained RhB amount of up to 2040 mg/g even after five cycles.